(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Restoring the tooth row with the help of implants instead of a lost tooth is different from other methods without damaging healthy teeth, but it does not always end successfully after the placement of implants, several reasons can be given, among which the thickness of the milik is of great importance.